Technical Efficiency of Sugar Cane Farming in PT PG Rajawali II Unit PG Sindanglaut - Eliah, Jian Fauzi Raisa; Daniswari, Adela; Dwirayani, Dina (Ann Publisher, 2024)
This research aims to determine the profitability and technical efficiency of sugarcane farming in PG Sindang Laut, Cirebon Regency, West Java. The research method used was survey research with 60 respondents of 30 plant cane and 30 ratoon cane. The data analysis used includes (1) descriptive analysis, (2) Cobb-Douglas production function with the SFA approach using Frontier 4.1, and (3) income analysis. The results of this research showed that, land area, seeds, phonska fertilizer, and labor affect sugar cane production in the plant cane category. On the other hand, land area, seeds, phonska fertilizer, and ZA fertilizer affect the technical efficiency of sugar cane farming of ratoon cane category. The factors that influence technical efficiency in the plant cane category are age, farming experience, and family responsibility. While education and farming experience influence technical efficiency in the ratoon cane category. The average income from sugarcane farming in the plant cane and ratoon cane categories is IDR 8,526,816/ha and IDR 13,195,410/ha.